Social Presence in the Web-based Synchronous Secondary Classroom - Nippard, Eric; Murphy, Elizabeth (Canadian Journal of Learning and Technology, 2007)
he purpose of the study reported on in this paper was to explore how teachers and students manifest social presence in the web-based synchronous secondary classroom (WBSSC). Data were collected using structured and unstructured observations of twelve online recordings of web-based synchronous classes in the province of Newfoundland and Labrador, Canada. Structured observations were guided by an instrument developed by Rourke, Anderson, Garrison and Archer (2001) for identifying and measuring social presence in an online context. Findings revealed that teachers and students relied on different tools when providing affective, interactive and cohesive responses related to social presence. Manifestations of social presence by the teachers occurred through use of two-way audio whereas students relied on text-based Direct Messaging. Expressions of social presence by the students and teachers occurred most often in a context of digressions that drew attention away from the delivery of content. In addition, students demonstrated social presence using discourse conventions transferred from informal social contexts of instant messaging such as ICQ and MSN. Résumé : L’objet de la présente étude consistait à examiner de quelle façon les enseignants et les étudiants font preuve de présence sociale dans les salles de classe synchrones en ligne du secondaire. Des données ont été recueillies au moyen d’observations structurées et non structurées provenant de douze enregistrements en ligne de classes synchrones accessibles par Internet dans la province de Terre-Neuve et Labrador, Canada. Les observations structurées ont été dirigées au moyen d’un instrument développé par Rourke, Anderson, Garrison, et Archer (2001) afin d’identifier et de mesurer la présence sociale en ligne. Les résultats démontrent que les enseignants et les élèves utilisent des outils différents pour offrir des réponses affectives, interactives et homogènes liées à leur présence sociale. Les manifestations de présence sociale par les enseignants se sont produites au moyen de l’utilisation d’un système de transmission audio bilatéral où les étudiants comptaient sur la messagerie texte directe. Les expressions de présence sociale des étudiants et des enseignants se produisent la plupart du temps dans un contexte de digressions qui fait en sorte qu’on s’éloigne du contenu. De plus, les étudiants ont fait preuve de présence sociale au moyen de conventions sur le discours provenant de contextes sociaux informels de messagerie instantanée comme ICQ et MSN.